An Empirical Analysis of Bibliotherapy and Self-Management Technique as a Tool for Life Satisfaction - Adegun, Adedunni Omowunmi; Oke, Daisi Idowu; Fashina, Abiola Yetunde (NIU Journal of Humanities, 2018)
Growing old  is not has fun as you can imagine, often times aging  brings is accompany with health problems, Financial issues and decreasing functional capacity which may affect the quality of life of the elderly. This study thus, examined the therapeutic effect of Bibliotherapy (BT) and Self-Management techniques on life satisfaction of the elderly. It further investigated the moderating effects of emotional intelligence on the dependent variable. A pretest-posttest, control group, quasi-experimental design with a3x3 factorial matrix was adopted. Ninety-three elderly (67 males and 26 females) were randomly selected from the three senatorial districts in Ondo State. Participants were randomly assigned into two treatment conditions (SM and BT) and control group. The training programmer lasted for eight weeks. Two research instruments were used; Satisfaction with Life Scale (Î±=0.74) and Emotional Intelligence Scale (Î± = 0.93). Three hypotheses were tested at Î±=0.05 level of significance.  Data were analysed using Analysis of Covariance.The result revealed that there was a significant main effect of treatments on life satisfaction (F (2, 75) =598.1, Î· 2 =0.941) of retirees. Further findings and implications of findings were discussed. Keywords: Bibliotherapy, self-management, life satisfaction, emotional intelligence, elderly